Childhood Traumatic Experiences and Negative Alcohol-Related Consequences in Adulthood: A Cross-Cultural Examination of Distress Tolerance and Drinking to Cope. (12th May 2023) - Norton, Emily O.; Hailemeskel, Ruth; Bravo, Adrian J.; Pilatti, Angelina; Kaimner, Debra; Conway, Christopher C.; Mezquita, Laura; Hogarth, Lee; ,
Abstract: Background: Prior research has established that Adverse Childhood Experiences (ACEs) predict harmful alcohol use outcomes. However, underlying mechanisms that could explain these associations are less clear. The present study examined if ACEs are indirectly related to alcohol negative consequences through their associations with distress tolerance and drinking to cope. Method: A sample of 3, 763 (71.9% female) college students who drink alcohol from seven countries (U.S., Argentina, Canada, Uruguay, Spain, South Africa, and England) completed online surveys. Path analysis was performed within the whole sample testing the serial unique associations between ACEs→distress tolerance→drinking to cope→negative alcohol-related consequences. Multi-group analysis was performed to determine if the proposed pathways were invariant across gender and countries. Results: Both distress tolerance and drinking to cope uniquely accounted for the relationship between ACEs and negative alcohol-related consequences. Additionally, a significant double-mediation effect was found illustrating that a higher endorsement of ACEs was associated with lower distress tolerance, which in turn was associated with higher drinking to cope, which in turn was associated with more negative alcohol-related consequences. These effects were invariant across countries and gender groups. Conclusions: These findings provide support for the relevance of distress tolerance and coping motives as potential factors in linking ACEs to problematic alcohol use across nations. Our data are consistent with the idea that intervening on distress tolerance and drinking motives could mitigate downstream alcohol-related consequences related to ACEs in college student populations around the world.